Sobre a carioquidade - Houaiss, Antônio (Ciência & Trópico, 2011)
RESUMOComo qualquer fato cultural, ser carioca é ser unidade de diversidade. Carioca como vocábulo é habitante branco de casa branca; é nome de um rio e, mais, de um largo – o Lar¬go da Carioca. A alma do carioca e o seu corpo têm sido buscado por homens que, a pretex¬to de fazerem ficção, captaram melhor que ninguém o incaptável por quem busca uma apre¬ensão física, psíquica e moral com que se possa retratar o carioca. O impulso da criatividade carioca em conexão com a vida erótica é superiormente manifesto na sua elaboração musical e na visão satírica de sua caricatura. O musical é faceta triste da carioquidade. O carioca, hoje, ainda que não queira consome alienação roqueira, sua alma musical veio do lundu e flo¬resceu nos seus múltiplos tipos de samba, de marcha, de canção, de modinha e desaparece ho¬je, sob o ruído dos Rocks in Rio.ABSTRACTAbout the “carioquidade”. v. 13, n. 1, p. 99-110, jan./jun. 1985.To be a “carioca” (man from Rio de Janeiro, as any cultural fact, is to be unity of diversities. The meaning of the word “carioca” is a white habitant of a white house; is name of a river and more, of a traffic island – the “Largo da Carioca”. “Carioca’s” soul and body have been searched by men, who trying to make fiction, they got better than anyone else the unreachable point, of whom searches a physical, psychic and moral aprehension that can give a “carioca’s” portrait. The “carioca” creative impulse in connection with the erotic life is superiorly shown in his musical elaboration and in the satirical vision of his caricature. The musical aspect is a sad facet of “carioquidade”. The “carioca”, of nowadays even without wanting it, receives the influence of the rock. His musical soul came from the “lundu” (a typical music that came from Africa) and flourished in several kinds of “samba”, march, song. and weakens today under the noise of the Rocks in Rio.*Carioquidade – character, formation, and way of being of the people from Rio de Janei¬ro.RÉSUMÉSur la “carioquidade”. v. 13, n. 1, p. 99-110, jan./ jun. 1985.Comme tout le fait culturel, être “carioca” c’est être unité dans la diversité. “Carioca” signifie habitant blanc de maison blanche; c’est le nom d’un fleuve, et plus d’un espace – le “Largo da Carioca”. L’âme du “carioca” et aussi son corps, ont été recherchés par des hommes, qui sous pretexte de faire de la fiction ont attiré l’attention sur l’inconcevable à tous ceux qui cherchent une apréhension physique, psychique et morale qui puisse faire le portrait du “carioca”. L’énergie de la création “carioca” liée à sa vie érotique, est supérieurement manifestée dans son élaboration musicale et dans la vision satirique de sa caricature. Le musicale est la triste facette de la “carioquidade”. Le “carioca” d’aujourd’hui, même sans attendre reçoit l’influence du rock. Son âme musicale est venue du “Lundu” et a fleuri dans les multiples types de samba, de marche, de chanson, de chansonnette et qui sont disparus aujourd’hui sons le bruit des “Rocks in Rio”.